An introduction to politics, state and society - McAuley, James W. 1956- (Sage Publications, 2003)
This text introduces the central theories and issues in current political sociology, and demonstrates that politics cannot be properly understood purely in terms of its institutions. It also enables students to learn the importance of the broader relationships between society, social structure and power